Risk factors of postoperative low cardiac output syndrome in children with congenital heart disease: A systematic review and meta-analysis - Wang, Peiying; Fu, Cangcang; Bai, Guannan; Cuan, Linbo; Tang, Xiaomin; Jin, Chendi; Jin, Hongchong; Zhu, Jihua; Xie, Chunhong (Frontiers in Pediatrics, 2023)
Background:Low cardiac output syndrome (LCOS) is the most common complication after cardiac surgery, which is associated with the extension of postoperative hospital stay and postoperative death in children with congenital heart disease (CHD). Although there are some studies on the risk factors of LCOS in children with CHD, an unified conclusion is lack at present. Purposes:To synthesize the risk factors of LCOS after CHD in children, and to provide evidence-based insights into the early identification and early intervention of LCOS. Methods:Four English and three Chinese databases were searched for relevant articles that were published between the establishing time of each database and January 2022. The reference list of the retrieved articles was also manually reviewed. This study followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The risk of bias was evaluated according to the Newcastle-Ottawa Scale (NOS). RevMan 5.4 software was used to conduct the meta-analysis. Results:A total of 1886 records were screened, of which 18 were included in the final review. In total, 37 risk factors were identified in the systematic review.Meta- analysis showed that age,type of CHD, reo-peration, biventricular shunt before operation, CPB time, aortic clamping time, postoperative residual shunt, cTn-1 level 2 hours after CPB > 14ng/ml and postoperative 24h MR-ProADM level > 1.5nmol/l were independent risk factors of LCOS. Additionally, the statistics of blood oxygen saturation before the operation was found to have no statistically significant relationship with LOCS. Conclusion：The risk factors of postoperative LCOS in children with CHD are related to disease condition, intraoperative time and postoperative related indexes, so early prevention should be aimed at high-risk children.